Depressive Language on a Virtual Common: A Critical Discourse Analysis - Aperocho, Maico Demi; Tarusan, Mary Ann E. (Future Science / FSH-PH Publications, 2022)
Language use is important in a community such as composed of people living with mental health conditions. The researcher aimed to understand depressive language more deeply by looking at the linguistic features, unravelling the process of language consumption as evidenced in the language experiences of depressed people, and determining the dominant ideological representations. Using the 3-Dimensional Framework of Critical Discourse Analysis, the researcher made a thorough investigation on depressive language on Facebook. In the textual analysis, it was revealed that depressive language contains certain linguistic features such as lexical items belonging to different categories, use of self-references, presence of positive and emotions words, and occurrence of words related to status, dominance, and social hierarchy. In the interview with seven depressed people, language experiences include the use of language for various purposes such as for expressing, fighting stigma, getting help, and educating other people. The participants also shared that language could be a reason for triggers and stigma. Based on the linguistic features and the language experiences, it was also found out that certain ideologies are dominant in depressive language such as the existence of stigma in society, death as an escape from pain, inevitability of sadness, and continuous seeking of help and attention. This study is deemed important in advancing more studies in the Philippine context focusing on mental health and language use.